Seis novas espécies de Neotrephes China, 1936 (Heteroptera: Helotrephidae) do Brasil, com uma chave para os Helotrephidae neotropicais (Lundiana: International Journal of Biodiversity, 2002)
Six new species of Neotrephes: N. fragosus sp. n., N. lanemeloi sp. n., N. latus sp. n., N. minutus sp. n., N. transversus sp. n. and N. variegatus sp. n. are described from the Brazilian state of Minas Gerais. A key to the species of American Helotrephidae is added.